2021
DOI: 10.1007/s11033-021-06800-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 derived cytokine storm on cancer cells progression: double-edged sword

Abstract: Objective Severe acute respiratory syndrome coronavirus 2 (SARS-COV2) was first detected in Wuhan, China in December, 2019. The emerging virus causes a respiratory illness, that can trigger a cytokine storm in the body. Method Cytokine storm in patient’s body is associated with severe forms of disease. It is one of the main complications of coronavirus disease-2019 (COVID-19), in which immune cells play a major role. Studies have shown immune cells in the tumor environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 111 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the indirect effect of the systematic inflammation due to the cytokine storm should be considered for thrombotic events. [ 29 33 ] It has been reported that chronic oral anticoagulation reduces all-cause mortality in COVID-19 patients. [ 34 ] In a review conducted by Gómez-Mesa et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the indirect effect of the systematic inflammation due to the cytokine storm should be considered for thrombotic events. [ 29 33 ] It has been reported that chronic oral anticoagulation reduces all-cause mortality in COVID-19 patients. [ 34 ] In a review conducted by Gómez-Mesa et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] In a review conducted by Gómez-Mesa et al . [ 33 ] on 1,099 patients, thrombocytopenia and elevation of D-dimer were reported to be the most consistent hemostatic alterations in COVID-19 infection, associated with a higher requirement for mechanical ventilation, admission to intensive care, and death. Initial anticoagulant treatment with low molecular weight heparin reduced mortality by 48% at 7 days and 37% at 28 days and significant improvement in the arterial oxygen pressure/inspired fraction of O2 (PaO2/FiO2) by mitigating the formation of microthrombi and pulmonary coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, chemotherapy in CLL and COVID-19 cases remains controversial, as it may increase the risk of cardiotoxicity, SARS-CoV-2-induced immunodeficiency, and prognosis [ 143 ]. To minimize treatment-induced immunodeficiency and drug interactions, it is therefore best to avoid chemotherapy in patients with comorbid CLL and COVID-19 [ 144 , 145 ].…”
Section: Haematological Malignancies and Covid-19mentioning
confidence: 99%